Existence of Solutions of the Nonautonomous Abstract Cauchy Problem of Second Order - Henriquez-Miranda, H (2013)
In this paper the existence of solutions of a nonautonomous abstract Cauchy problem of second order is considered. Assuming appropriate conditions on the operator of the equation, we establish the existence of mild solutions and, in some cases, we construct an evolution operator associated to the homogeneous equation. Using this evolution operator we obtain existence of solutions for the inhomogeneous equation. Finally, we apply our results to study the existence of solutions of the nonautonomous wave equation. © 2013 Springer Science+Business Media New York.